পার্লামেন্টারি শব্দকোষ - ফিরোজ, জালাল.; বাংলা একাডেমী (Bangladesh) (ঢাকা : বাংলা একাডেমী, 1998)
Dictionary of parlimentary terms, with reference to Bangladesh.
Includes bibliographical references (p. [290]-293) and index.
Bengali and English.
Keywords: Bangladesh. -- Jātīẏa Saṃsada -- Terminology; Parliamentary practice -- Bangladesh -- Dictionaries